FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEPUASAN NASABAH BANK RAKYAT INDONESIA (BRI) CABANG SAMARINDA - Zulfikar Zulfikar; Chottam Chottam; Florentina Kohat; Dimas Riski Efendi (Politeknik Negeri Samarinda, 2021)
This research aims to providing services that benefit customers. The purpose of this study was to examine customer satisfaction partially and simultaneously the role of customer service at PT Bank Rakyat Indonesia Samarinda Branch Office 1. Instruments for collecting data in the form of questionnaires measured by Likert Scale.The sample in this study was 350 customers of PT Bank Rakyat Indonesia Samarinda Branch Office 1 which was carried out randomly using probability sampling techniques. The data analysis method was tested with Statistical Product and Service Solution (SPSS) which included validity, reliability testing, simple regression analysis hypothesis testing via t test and analysis of the coefficient of determination (R2). This study consists of two hypotheses and the results of two hypotheses show that the role of Customer Service (X) has been shown to have a positive and significant effect on customer satisfaction (Y). At PT Bank Rakyat Indonesia Samarinda Branch 1. Keywords: The Role of Customer Service, Customer Satisfaction.